Procedural Law of Ancient Rome in the Imperial Period - D. V. Slynko (Bulletin of Kharkiv National University of Internal Affairs)
The scientific study is devoted to the consideration of procedural law in ancient Rome during the reign of the kings. It is noted that scientific research is usually devoted to the problems of substantive law, both civil and family law, and procedural law and its institutions have been considered by legal scholars much less frequently. The article examines the governing bodies of the Roman State, namely, the People’s Assembly, the king (rex) and the Senate. It is noted that at any time the People's Assembly could remove the king from office, i.e. he cannot be called an absolute monarch. The king was a military commander, a priest, who dealt with the day-to-day management of the polis-state and acted as the supreme judge. The boundaries of the governing bodies of Ancient Rome, their competence and powers were established by custom. Customs were the first source of law in ancient Rome, which regulated relations within the family and community with the help of religious norms and social principles. Later, customs were recognised and enforced by the state. The collection of the most widespread and applied customs, the Laws of the XII Tables, was approved by the People's Assembly in 451–450 BC.